Assessment of self-reported sexual behavior and condom use among female sex workers in India using a polling box approach: a preliminary report. - Hanck, Sarah E; Blankenship, Kim M; Irwin, Kevin S; West, Brooke S; Kershaw, Trace (Sexually transmitted diseases, 2008)
The accuracy of behavioral data related to risk for HIV and other sexually transmitted infections is prone to misreporting because of social desirability effects. Because computer-assisted approaches are not always feasible, a noncomputerized interview method for reducing social desirability effects is needed. The previous performance of alternative methods has been limited to aggregate data or constrained by the simplicity of dichotomous-only responses. We designed and tested a "polling box" method for case-attributable, multiple-response survey items in a low literacy population.
Keywords: Adolescent; Adult; Condoms; Cross-Sectional Studies; Delivery of Health Care; Female; Humans; India; Logistic Models; Preventive Health Services; Prostitution; Questionnaires; Sexual Behavior; Sexually Transmitted Diseases